Effects of benfotiamine and coenzyme Q10 on kidney damage induced gentamicin - Ustuner, Mehmet Alperen; Kaman, Dilara; Colakoglu, Neriman (Churchill Livingstone, 2017)
Objective: Gentamicin (GM) is an effective antibiotic against severe infection but has limitations related to nephrotoxicity. In this study, we investigated whether benfotiamine (BFT) and coenzyme Q10 (CoQ10), could ameliorate the nephrotoxic effect of GM in rats. Methods: Rats were divided into five groups. Group 1 and 2 served as control and sham respectively, Group 3 as GM group, Group 4 as GM + CoQ10 and Group 5 as GM + BFT for 8 days. At the end of the study, all rats were euthanized by cervical decapitation and then blood samples and kidneys were collected for further analysis. Serum urea, creatinine, cytokine TNF-alpha, oxidant and antioxidant parameters, as well as histopathological examination of kidney tissues were assessed. Results: Gentamicin administration caused a severe nephrotoxicity which was evidenced by an elevated serum creatinine, urea and KIM-1 level as compared with the controls. Moreover, a significant increase in serum malondialdehyde, reduced glutathione. Histopathological examination of renal tissue in gentamisin administered group, there were extremly pronounced necrotic tubules in the renal cortex and hyalen cast accumulation in the medullar tubuli. BFT given to GM rats reduced these nephrotoxicity parameters. Serum creatinine, urea, and KIM-1 were almost normalized in the GM + BFT group. Benfotiamin treatment was significantly decreased necrotic tubuli and hyalen deposition in gentamisin plus benfotiamin group. CoQ10 given to GM rats did not cause any statistically significant alterations in these nephrotoxicity parameters when compared with GM group but histopathological examination of renal tissue in GM + CoQ10 administered group, CoQ10 treatment was decreased necrotic tubuli rate and hyalen accumulation in tubuli. Conclusion: The results from our study indicate that BFT supplement attenuates gentamicin-induced renal injury via the amelioration of oxidative stress and inflammation of renal tubular cells.
Keywords: Benfotiamine; Coenzyme Q10; Nephrotoxicity; Oxidative stress